Analisis Kesalahan Siswa dalam Menyelesaikan Soal Keliling dan Luas Lingkaran - Nurul Fazri Harahap; Aliskha Zuhra; Andin Mutia Wardana; Ramadhani Ramadhani (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2025)
Mathematics plays an important role in training critical and logical thinking skills. One topic that is often applied in everyday life is the circumference and area of ​​a circle. However, many students have difficulty understanding and solving word problems related to this topic. This research aims to identify the types of errors made by students in solving circumference and area of ​​circle problems and analyze the causal factors. This research uses a qualitative method with a descriptive approach. The research subjects were 16 class IX students at MTs Al-Habibi who were selected using a purposive sampling technique. Data was collected through a test containing five story questions with varying levels of difficulty and analyzed based on four categories of errors, namely concepts, facts, principles, and procedural. The research results showed that the majority of students had difficulty understanding the questions, identifying problems, and applying concepts correctly. As many as 68.75% of students scored below the KKM, indicating low understanding. Factors that cause errors include limited understanding of basic concepts, low learning motivation, and less interactive teaching methods. More effective learning strategies are needed, such as interactive methods, gradual practice, and strengthening concepts before complex questions. With the right strategy, students' understanding of the circumference and area of ​​circles can increase, so they are better prepared to solve story problems.